EXPLORING HUMAN CAPITAL DALAM TINGKAT PENDIDIKAN PERAN APLIKASI SISTEM INFORMASI AKUNTANSI MENGATASI DETEKSI FRAUD PADA APLIKASI SHOPEE - Hertati, Lesi; Yadiati, Winwin (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
This research aims to explore the importance of human capital such as level of education, understanding and expertise in order to detect fraud in accounting information system software in order to detect fraud. The success of an accounting information system in detecting and preventing fraud does not only depend on technology, but also on the quality of human resources involved in the use, management and development of the system. This study uses descriptive and verification analysis of the role and contribution of human capital, such as knowledge, skills and attitudes, in increasing users of accounting information systems related to fraud detection in the Shopee application. Data was collected through interviews with Indo Global Mandiri University students who use Shopee. The analytical tool used in this research is SEM PLS. The research results prove that understanding of finance, knowledge of information technology, and high analytical skills of human resources can detect fraud in the Shopee application. The research results prove that human capital can be the key to success in increasing the level of education related to accounting information systems that focus on fraud detection in the Shopee application. The role of effective human capital is to increase resilience to potential fraud risks in an increasingly complex business environment.